The policy framework of Euro-Med cooperation on research and innovation. Effects on research collaborations - Arvanitis R.; Rodriguez Clemente R.; El-Zoheiry A.H. (Moving forward in the Euro-Mediterranean Research and Innovation partnership. The experience of the MIRA project, 2013)
This article analyzes the policy framework that affects the Euro-Mediterranean research cooperation, since the Barcelona declaration of 1995 until the more recent Neighbourhood policy of the EU. We examine the policy orientations and its changes, the effect on scientific collaborations in terms of publications and number of collaborations as measured by the MIRA Survey. We try to examine the effects in terms of governance of research collaborations. We also compare the EU sponsored research programmes to the bilateral collaborations. Finally we identify a series of proposals in order to generate a co-funded and co-decided partnership.